Levels of burn-out among healthcare workers during the COVID-19 pandemic and their associated factors: a cross-sectional study in a tertiary hospital of a highly burdened area of north-east Italy. Issue 1 (17th January 2021) - Lasalvia, Antonio; Amaddeo, Francesco; Porru, Stefano; Carta, Angela; Tardivo, Stefano; Bovo, Chiara; Ruggeri, Mirella; Bonetto, Chiara
Abstract : Objective: To determine burn-out levels and associated factors among healthcare personnel working in a tertiary hospital of a highly burdened area of north-east Italy during the COVID-19 pandemic. Design: Observational study conducted from 21 April to 6 May 2020 using a web-based questionnaire. Setting: Research conducted in the Verona University Hospital (Veneto, Italy). Participants: Out of 2195 eligible participants, 1961 healthcare workers with the full range of professional profiles (89.3%) completed the survey. Primary outcome measure: Levels of burn-out, assessed by the Maslach Burnout Inventory-General Survey (MBI-GS). Multivariable logistic regression analysis was performed to identify factors associated with burn-out in each MBI-GS dimension (emotional exhaustion, EX; professional efficacy, EF; cynicism, CY). Results: Overall, 38.3% displayed high EX, 46.5% low EF and 26.5% high CY. Burn-out was frequent among staff working in intensive care units (EX 57.0%; EF 47.8%; CY 40.1%), and among residents (EX 34.9%; EF 63.9%; CY 33.4%) and nurses (EX 49.2%; EF 46.9%; CY 29.7%). Being a resident increased the risk of burn-out (by nearly 2.5 times) in all the three MBI subscales and being a nurse increased the risk of burn-out in the EX dimension in comparison to physicians. Healthcare staff directly engaged with patients with COVID-19 showed more EX and CY than those working in non-COVID wards. Finally, the risk of burn-out was higher in staff showing pre-existing psychological problems, in those having experienced a COVID-related traumatic event and in those having experienced interpersonal avoidance in the workplace and personal life. Conclusions: Burn-out represents a great concern for healthcare staff working in a large tertiary hospital during the COVID-19 pandemic and its impact is more burdensome for front-line junior physicians. This study underlines the need to carefully address psychological well-being of healthcare workers to prevent the increase of burn-out in the event of a new COVID-19 healthcare emergency.